Influence of activation conditions on the compressive strength, microstructure, and reaction products of sugarcane bagasse ash cements - Espinoza Pérez, Lester Javier; Zuniga García, Zugania Zelmira (Nexo Revista Científica, 2022)
Pastes of sugarcane bagasse ash (SCBA) and calcium aluminate cement (CAC) were activated with sodium silicate solutions, varying the SCBA content (80-95 wt.%), the SiO2/Na2O ratio (8-14 wt.% respect to the weight of SCBA), and the curing temperature (20 and 40 ºC or 100 and 200 ºC). 28 days-compressive strength between 5-20 MPa were obtained. The results are close to the reported in the literature for pastes of SCBA/metakaolin. Overall, it was observed that the compressive strength decreased with the increase in the curing temperature from 100 to 200 ºC. The gain in the compressive strength was attributed to the formation of a dense matrix of amorphous reaction products such as C-S-H, N-A-S-H, C-A-S-H, or silica gel. Our results stress the feasibility to use higher contents of sugarcane bagasse ash to obtain alkali-activated cement with compressive strengths up to 20 MPa. Further work is currently underway to identify the effect of some variables on the compressive strength of composites.